2017
DOI: 10.1021/acschemneuro.7b00318
|View full text |Cite
|
Sign up to set email alerts
|

Altered Volatile Organic Compound Profile in Transgenic Rats Bearing A53T Mutation of Human α-Synuclein: Comparison with Dopaminergic and Serotonergic Denervation

Abstract: Early diagnosis of Parkinson's disease (PD) is of great importance due its progressive phenotype. Neuroprotective drugs could potentially slow down disease progression if used at early stages. Previously, we have reported an altered content of volatile organic compounds (VOCs) in the breath of rats following a 50% reduction in striatal dopamine (DA) content induced by 6-hydroxydopamine. We now report on the difference in the breath-print and content of VOCs between rats with mild and severe lesions of DA neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The authors showed that increased levels of benzaldehyde in PD patients, together with acetophenone, are a molecular signature differentiating PD and control individuals. This study, along with the authors' previous work in animal models, 12 demonstrates the potential of sensor arrays to detect PD. Rare individuals with highly discriminatory olfaction have also recently been found to identify PD patients, even prior to clinical diagnosis (McFadden, J., The Telegraph, December 19, 2017).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The authors showed that increased levels of benzaldehyde in PD patients, together with acetophenone, are a molecular signature differentiating PD and control individuals. This study, along with the authors' previous work in animal models, 12 demonstrates the potential of sensor arrays to detect PD. Rare individuals with highly discriminatory olfaction have also recently been found to identify PD patients, even prior to clinical diagnosis (McFadden, J., The Telegraph, December 19, 2017).…”
supporting
confidence: 63%
“…This study, along with the authors’ previous work in animal models, demonstrates the potential of sensor arrays to detect PD. Rare individuals with highly discriminatory olfaction have also recently been found to identify PD patients, even prior to clinical diagnosis (McFadden, J., The Telegraph , December 19, 2017).…”
mentioning
confidence: 99%
“…7−13 In an animal model, the system successfully discriminated between serotonergic and dopaminergic denervations, as well as between transgenic rats bearing α-synuclein A53T mutation and wild-type controls. 14 In our previous clinical study, the classification of established PD patients and control subjects resulted in a sensitivity of 70%, specificity of 100%, and accuracy of 79%, based on the pattern response of the sensors. 7 More recently, using the same sensor array, we established the ability of the system to distinguish between iPD and parkinsonism of various etiologies with a sensitivity and accuracy of 88%.…”
mentioning
confidence: 95%
“…To date, despite advances in the field, PD diagnosis remains subject to a high degree of error. ,, In a recent study only 26% of PD cases at first presentation were positively identified as iPD by subsequent neuropathological techniques. Previously, we have reported, in both preclinical and clinical studies, that the exhaled breath volatolome (the spectrum of exhaled volatile organic compounds, VOCs) is significantly altered in neurodegenerative diseases. Moreover, a sensor array that is based on organically functionalized random networks of single-walled carbon nanotubes or gold nanoparticles could be trained via machine learning methods to detect these changes. In an animal model, the system successfully discriminated between serotonergic and dopaminergic denervations, as well as between transgenic rats bearing α-synuclein A53T mutation and wild-type controls . In our previous clinical study, the classification of established PD patients and control subjects resulted in a sensitivity of 70%, specificity of 100%, and accuracy of 79%, based on the pattern response of the sensors .…”
mentioning
confidence: 99%
“…Electronic noses have shown promising results in the detection of many types of tumors (colorectal, lung, prostate, gastric, and head and neck cancer) as well as for early diagnosis of other diseases like Parkinson disease. [8][9][10][11][12] Yet, there are no studies reporting on the use of e-nose technology to detect cervical HSIL.…”
mentioning
confidence: 99%